AN ANALYSIS OF GOTTLIEB'S SUBTITLING STRATEGIES: COMPARING THE OFFICIAL AND NON-OFFICIAL SUBSTILES OF ZOOTOPIA MOVIE - Fikri, Haris Chaerul (2017)
The study is aimed to compare the official and non-official Indonesian subtitles that are used in Zootopia movie as well as to analyze, investigate, and elaborate the strategies employed by the official and non-official subtitles. Employing a qualitative approach and comparative method, this study uses Gottlieb's (1992) ten subtitling strategies to find the similarities and differences in the official and non-official Indonesian subtitles. In term of similarities, the result shows that there are 511 utterances that are translated by using similar strategies and 531 utterances using different strategies. The differences can be found when the utterances contain a word that refers to an object, cultural words, proper names, and insult words. Additionally, the differences also occur in the degree of formality, careful use of punctuation, precision of translation, and subjectivity of the translation.;--- Penelitian ini ditujukan untuk membandingkan terjemahan Bahasa Indonesia resmi dan tidak resmi pada film Zootopia juga untuk menganalisa, menyelidiki, dan mengelaborasi strategi yang digunakan pada terjemahan resmi dan tidak resmi. Dengan menggunakan pendekatan kualitatif dan metode komparatif, penelitian ini menggunakan teori Gottlieb (1992) tentang sepuluh strategi terjemahan untuk menemukan persamaan dan perbedaan pada terjemahan Bahasa Indonesia resmi dan tidak resmi. Dalam hal persamaan, hasil penelitian ini menunjukkan bahwa terdapat 511 ucapan yang diterjemahkan dengan menggunakan strategi yang sama dan 531 ucapan dengan menggunakan strategy yang berbeda. Perbedaannya dapat ditemukan ketika sebuah ucapan mengandung kata yang mengacu terhadap sebuah objek, kata-kata kultural, nama identitas, dan kata-kata penghinaan. Tambahan, perbedaan itu pun juga muncul pada tingkat formalitas, penggunaan tanda baca yang hati-hati, ketepatan dalam penerjemahan, dan subjektifitas pada terjemahan.